2017
DOI: 10.1080/02673843.2017.1337585
|View full text |Cite
|
Sign up to set email alerts
|

The lifetime prevalence of exposure to community violence among Lebanese university students: association with behavioural and mental health correlates

Abstract: Studies that examine the exposure to community violence (CVE) among young adults in developing countries are limited. This study aimed at estimating the prevalence and types of CVE and its behavioural and mental health correlates among Lebanese university students. In this cross-sectional study, a total of 450 university students were sampled using proportionate sampling design. Overall, 70.3% of the sample reported witnessing violence and 49.1% violence victimization. The most common type of witnessing commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Previous research conducted in Lebanon generally suggests that women are especially prone to psychological distress (Ayyash-Abdo & Alamuddin, 2007; Barbour et al, 2012). However, Itani et al (2018) found a 70% prevalence of exposure of community violence in Lebanese young adults (both men and women), which was also associated with psychological distress. Moreover, communal tensions and violence, war, and the COVID-19 pandemic and recent explosion in Beirut are likely to affect the entire population.…”
Section: A Theoretical Model Predicting Coping Stylesmentioning
confidence: 99%
“…Previous research conducted in Lebanon generally suggests that women are especially prone to psychological distress (Ayyash-Abdo & Alamuddin, 2007; Barbour et al, 2012). However, Itani et al (2018) found a 70% prevalence of exposure of community violence in Lebanese young adults (both men and women), which was also associated with psychological distress. Moreover, communal tensions and violence, war, and the COVID-19 pandemic and recent explosion in Beirut are likely to affect the entire population.…”
Section: A Theoretical Model Predicting Coping Stylesmentioning
confidence: 99%
“…There has been some work on the impact of violence on psychological health, including the onset of psychological distress (e.g. Abu-Saba, 1999;Itani, Fischer and Chu, 2018). Although there is no research into psychological distress among nonheterosexual people in Lebanon, there is evidence from other countries that non-heterosexual people are at increased risk of psychological distress, due largely to preventable situational stressors.…”
Section: Psychological Distressmentioning
confidence: 99%
“…Previous studies consistently reported that community violence is associated with many physical, psychological, or developmental problems (DeCou & Lynch, 2017;Itani et al, 2018;Overstreet, 2000). Those exposed to community violence were often physically injured, had head trauma, and applied to the emergency units of hospitals (Jaycox et al, 2004;Sutherland et al, 2002).…”
Section: Consequencesmentioning
confidence: 99%